Influence of different rice establishment methods and nutrient levels on soil enzyme activity, nutrient status and grain yield of rice in North Coastal Zone of Andhra Pradesh - Rama Lakshmi, Ch S; Kumari, MBGS; Sreelatha, T; Sireesha, A (ORYZA-An International Journal of Rice, 2019)
To enhance productivity, alleviate environmental and management constraints and enhance farmers’ income inÂ the rice, new approaches that are labour-saving, more productive and sustainable need to be developed.Â Experiment was formulated to know the impact/influence of different rice establishment methods and differentÂ levels of nitrogen application on soil and crop productivity of rice. Results revealed that, among different riceÂ establishment systems, machine transplanting recorded significantly higher yields followed by SRI method. Lowest yields were recorded in dry seed broadcasting method. With increasing nitrogen levels, yields wereÂ increased in all the systems and further enhancement of rice yields were observed with potassium nitrate foliar spray along with chemical fertilizers. Soil enzyme activity particularly urease and dehydrogenase wasÂ significantly high under normal planting and SRI method of planting, respectively and lowest enzyme activitiesÂ were recorded in broadcasting of dry seed. Soil organic carbon content also followed the same trend as likeÂ enzyme activity. With regard to soil nutrient status, significant differences were not observed in phosphorus andÂ potassium, however available nitrogen status was increased with increasing fertilizer levels and among differentÂ methods, drum seeding recorded highest status (286 kg ha-1).